Components of speaking skills that influence sophomore high school students’ spoken english abilities at Unidad Educativa Particular Santa Ana in the year 2022. - Méndez Benavides, Karla Adriana (2023)
Speaking is considered to be one of the hardest abilities to master when learning a foreign language, and English is no exception. The main goal of this research project is to identify the influence of the speaking components that affect verbal communication on second baccalaureate students from the Unidad Educativa Santa Ana (UEPSA). The study has both quantitative, and qualitative instruments, including an interview and two diagnostic tests, that will allow a greater outlook on the factors that play a part in the student’s speaking abilities. Through the analysis of the data obtained it is possible to state that the components of speaking affect the English oral production of the students. Other findings reveal that most of the students present issues in vocabulary, fluency, and comprehension, likewise, introversion, studentteacher ratio, and time also play a role in the student’s performance. To tackle these factors, a proposal that recommends the use of debates to improve verbal communication has been developed.